The bias and efficiency of the ECB inflation projections: A state dependent analysis - Eleonora Granziera; Pirkka Jalasjoki; Maritta Paloviita (Norges Bank, 2021)
We test for bias and efficiency of the ECB inflation forecasts using a confidential dataset of ECB macroeconomic quarterly projections. We investigate whether the properties of the forecasts depend on the level of inflation, by distinguishing whether the inflation observed by the ECB at the time of forecasting is above or below the target. The forecasts are unbiased and efficient on average, however there is evidence of state dependence. In particular, the ECB tends to overpredict (underpredict) inflation at intermediate forecast horizons when inflation is below (above) target. The magnitude of the bias is larger when inflation is above the target. These results hold even after accounting for errors in the external assumptions. We also find evidence of inefficiency, in the form of underreaction to news, but only when inflation is above the target. Our findings bear important implications for the ECB forecasting process and ultimately for its communication strategy.
hdl:11250/2755864
Keywords: C12; C22; C53; E31; E52; 330; Forecast Evaluation; Forecast Efficiency; Inflation Forecasts; Central Bank Communication